Prevalence of Acute Abdomen Admission in Surgery Ward at Tertiary Care Center of Nepal - Poudel, Rajesh; Chandra, Kailash; Shah, Santosh; Mahasheth, Naveen; Mishra, Santosh; Paudel, Kumar (Journal of Universal College of Medical Sciences, 2019)
INTRODUCTION: Abdominal pain is one of the most common reasons for an emergency department visit, accounting to about 8% of all emergency visits in United States. There are very few data available regarding the emergency admission of acute abdomen in Nepal. The aim of this study is to determine the prevalence of acute abdomen admission and their frequency according to the age, sex and month of admission in hospital. MATERIAL AND METHODS: This was a retrospective descriptive study carried out in Universal College of Medical Sciences, Bhairahawa, Nepal. Admission registers of surgery ward from July 2017 to June 2018 were reviewed. Data regarding the diagnosis, age, sex and month of admission of the patients were collected. Descriptive analyses were done regarding the frequency of disease, distribution of the diseases according to the age, sex and month of occurrences. RESULTS: Total of 675 patients with acute abdomen were analyzed. Acute appendicitis was the most common cause for acute abdomen accounting for 52% of total admission. It was followed by intestinal obstruction (13%) and acute cholecystitis (11%). Median age of presentation of acute appendicitis was 23 years. Median age of presentation of acute cholecystitis was 42 years. Acute abdomen occured most frequently on April, May and December. Overall, spring season had highest number of admission (31.5%) followed by winter (25.6%). CONCLUSION: Acute abdomen incidence varies according to age, most commonly found in young adults. Male has higher prevalence of acute abdomen when compared to female with exception of acute cholecystitis.